Guinea : Fifth Review Under the Three-Year Arrangement Under the Extended Credit Facility, Financing Assurances Review, and Requests for an Augmentation of Access and Extension of the Current Arrangement. (IMF Staff Country Reports; Country Report, 2015)
This paper discusses Guinea's Fifth Review Under the Three-Year Arrangement Under the Extended Credit Facility (ECF), Financing Assurances Review, and Requests for an Augmentation of Access and Extension of Current Arrangement. Performance under the ECF program has been satisfactory. All quantitative performance criteria have been met. Macroeconomic policies in 2015 will remain supportive to help deal with the Ebola outbreak. The IMF staff supports the completion of the fifth review under the ECF arrangement and financing assurances review and requests for an extension of the current arrangement to end-2015, an augmentation in access, and disbursement of 25 percent of quota as budget support under the 5th review.